Pengaruh Suplementasi Lemak Terproteksi Terhadap Konsumsi dan Kecernaan Nutrien Sapi Perah Friesian Holstein - Pramono, Ahmad; Yusuf, Aditya; Widyawati, Susi Dwi; Hartadi, Hari (Universitas Sebelas Maret (UNS), 2018)
The research aims to evaluate protected fat supplementation to Friesian Holstein (FH) dairy cattle digestibility based on diet digestibility (dry matter and organic matter consumption; dry matter and organic matter digestibility). The reseach was conducted for 12 weeks, at the Breeding Center for Dairy Cattle (BBPTU-SP) Baturraden. The material used is 12 FH dairy cows. The experiment consists of two treatment i.e. P0: basal diet and P1: basal diet + 3% protected fat supplementation. Each treatment was repeated 6 times. Data were analyzed by independent samples t-test analysis. Result showed that fat protected supplementation had no effect on dry matter and organic matter consumption; dry matter and organic matter digestibility.